ANALISIS PENGGUNAAN APLIKASI ZOOM OLEH GEREJA KRISTUS RAHMANI INDONESIA JEMAAT DIASPORA CAWANG UNTUK PEMBELAJARAN ALKITAB SETELAH PANDEMI COVID-19 - Ratu Eda, Yohanes (STT Ekklesia Pontianak, 2023)
This study was carried out with the aim of analyzing the use of the virtual zoom application after the Covid-19 pandemic in Bible learning activities at the Indonesian Christ Rahmani Church, Cawang Diaspora Congregation. Using a descriptive qualitative method approach, and collecting data through various books including the Bible, journals and interviews, as well as various documents that are related to the topic studied in this writing. The order disrupted by the global pandemic of the new coronavirus (COVID-19) has now been declared over and has entered the epidemic stage. Indeed, there are pros and cons among churches regarding the use of the virtual zoom meeting application for activities organized by the church. Each group has its own arguments. However, the church must continue to study the Bible to increase people's faith in the Lord Jesus Christ. The conclusion obtained is that the use of the virtual zoom meeting application in studying the Holy Bible or Bible study after the Covid 19 pandemic is very good and satisfying and will continue to be maintained. Kajian ini dilakukan bertujuan untuk menganalisis penggunaan aplikasi virtual zoom pasca pandemi covid 19 pada kegiatan pembelajaran Alkitab di Gereja Kristus Rahmani Indonesia Jemaat Diaspora Cawang. Menggunakan pendekatan metode kualitatif deskriptif, serta mengumpulkan data melalui berbagai buku termasuk Alkitab, jurnal jurnal maupun wawancara, serta berbagai dokumen yang mempunyai keterkaitan dengan topik yang menjadi kajian dalam penulisan ini. Tatanan yang terganggu oleh pandemi global virus corona baru (COVID-19) kini telah dinyatakan berakhir dan telah memasuki tahap epidemi. Memang ada pro dan kontra di kalangan gereja terkait dengan pemakaian aplikasi virtual zoom meeting pada kegiatan-kegiatan yang diselenggarakan oleh gereja. Masing-masing kelompok memiliki argumentasi tersendiri. Namun, gereja harus terus mempelajari Alkitab untuk meningkatkan keimanan umat kepada Tuhan Yesus Kristus. Kesimpulan yang diperoleh bahwa penggunaan aplikasi virtual zoom meeting dalam pembelajaran kitab suci atau penelaahan Alkitab pasca pandemi covid 19 sangat bagus dan memuaskan serta terus dipertahankan.